Method for the Optimal Design of Vacuum-Evaporative Heat Pumps - Kuznetsov, M.A.; Tarasova, V.A.; Kharlampidi, D.Kh. (Проблеми машинобудування, 2019)
A method is developed for optimally designing vacuum-evaporative heat pumps that use water (R718) as a refrigerant. This method is based on the autonomous method of the thermoeconomic optimization of thermodynamic systems, and makes it possible, when optimizing the design and choosing economical modes of system operation, to simultaneously take into account both thermodynamic and economic parameters. На базі автономного методу термоекономічної оптимізації термодинамічних систем розроблена методика оптимального проектування вакуумно-випарних теплових насосів, що використовують воду (R718) як холодоагент. Ця методика дозволяє під час оптимізації конструкції і вибору економічних режимів роботи системи одночасно враховувати як термодинамічні, так і економічні параметри. На базе автономного метода термоэкономической оптимизации термодинамических систем разработана методика оптимального проектирования вакуумно-испарительных тепловых насосов, использующих в качестве хладагента воду (R718). Эта методика позволяет при оптимизации конструкции и выборе экономичных режимов работы системы одновременно учитывать как термодинамические, так и экономические параметры.